PROSPECTS FOR THE STUDY OF NARRATIVE - Berdieva , Oyjamol Erkinovna (Educational Research in Universal Sciences, 2023)
This article refers to the study of narratives as an important field that can help us better understand ourselves, our communities, and the world around us, and is provided with detailed information. It also describes the possibilities for studying narratives as new technologies that enable us to engage with narratives in innovative ways, such as the digital humanities. According to the study, exposure to a narrative can enhance empathy and hone critical thinking skills. It is a universal form of communication in which we all participate, whether we are sharing our personal experiences or enjoying a novel or movie. Through this investigation, we can gain a deeper understanding of how narrative shapes our understanding of the world around us. We can also learn techniques for crafting compelling stories that engage our audience and leave a lasting impact. Overall, the study of narrative promises to be a fascinating field of study for years to come.